Identification of a Potential SNP Related to the Expression of Immune Genes and Its Possible Application to Selection of WSSV-Resistant Pacific White Shrimp (Litopenaeus vannamei) - Bagus Rahmat Basuki; Alimuddin Alimuddin; Dinar Tri Soelistyowati; Sri Nuryati (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research